Desenvolvimento, caracterização e aplicação de novos catalisadores poliméricos heterogêneos baseados em poliestireno sulfonado e polissulfona para produção de biodiesel metílico a partir do ácido oleico - Lima, Ana Paula de (2018)
The production of biodiesel by esterification is a promising route, since it does not involve the generation of effluents, it is not necessary a strict control of the raw quality material in terms of free fatty acids and there is no contamination of the biodiesel by glycerine, since the by-product is water. In this work heterogeneous acids catalysts are used due to the numerous advantages when compared to the homogeneous ones, such as ease of use, reduction of corrosion, reduction of biodiesel purification stages. Catalysts polymer polysulfone (PSF) and sulfonated polystyrene (PSS) were prepared to catalyze the esterification reaction of oleic acid with methanol, producing biodiesel. Several morphological types of membranes were obtained by casting or eletrospinning. As reaction conditions for the production of biodiesel were: temperature of 100 ° C, molar ratio of 10: 1 (methanol: oleic acid), 5 % catalyst and various reaction times: 10 min, 30 min, 60 min, 90 min, 120 min, 240 min, 360 min, 480 min e 600 min. The presence of fibers, pores or homogeneity in the structure in the membranes was confirmed by SEM. Thermal stability and behavior were verified by TGA / DTG and DSC. By the BET and BJH methods it was possible to obtain the surface area of the membranes, volume and pore size. The conversion to biodiesel is defined by the FTIR bands and GC. For the membranes presenting the PSS, 10 minutes of reaction are sufficient to obtain a significant yield. The use of PSF resulted in greater termic stability for the PSF_PSS polymer blends. The PSF_PSS eletrospinning membrane presents a better conversion in methyl oleate, 70.5 % with only 10 minutes of reaction, this value increased to 95.8 % with 240 minutes of reaction. Considering the performance of the heterogeneous catalysts described in the literature, the results obtained are significant in relation to reaction time and process conversion.